Water and Climate Adaptation Plan for the Sava River Basin : Annex 6. Guidance Note on Economic Evaluation of Climate Change Impacts in the Sava River Basin - World Bank Group (World Bank, Washington, DC, 2015)
This report presents the water and climate adaptation plan (WATCAP) developed for the Sava river basin (SRB) as result of a study undertaken by the World Bank. The WATCAP is intended to help to bridge the gap between the climate change predictions for the SRB and the decision makers in current and planned water management investment projects that will be affected by changing climate trends. The purpose of the report is to: (i) assist stakeholders and decision makers in assessing and planning for the risks generated by climate change impacts on water resources; (ii) provide a basis for future plans and studies of adaptation to climate change impacts in the SRB; and (iii) stimulate cooperation and debate across the basin toward additional and more detailed studies on climate change impacts at the regional and basin scale. The SRB is projected to experience small increases in water use by the public water supply, industry, energy, and agricultural and irrigation sectors. However, it is widely expected that new hydropower plants (HPPs) will be constructed in the near future, making energy (primarily through hydropower) the most important water use in the SRB.